2008
DOI: 10.1074/jbc.m803139200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D Is a Positive Regulator of Bit1 Apoptotic Function

Abstract: Bit1 (Bcl-2 inhibitor of transcription) is a mitochondrial protein that induces caspase-independent apoptosis upon its release into the cytoplasm. Bit1 is primarily associated with anoikis (cell death induced by detachment from the extracellular matrix), because the apoptotic function of Bit1 is inhibited by integrin-mediated cell attachment but not by many other antiapoptotic treatments. Here, we show that protein kinase D (PKD) regulates Bit1 apoptotic function. Overexpression of constitutively active PKD or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…When cells lose their attachment to the underlying ECM and no integrin is ligated, Bit-1 is released from mitochondria into the cytoplasm where it binds to the proapoptotic AES-TLE complex and enhances anoikis (11). This may be due to phosphorylation of Bit-1 by other signaling molecules such as PKD1 (13). However in cells attached to fibronectin, Bit-1 works in conjunction with a FAK/PI3K/NFB signaling pathway and elevates bcl-2 transcription to promote cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When cells lose their attachment to the underlying ECM and no integrin is ligated, Bit-1 is released from mitochondria into the cytoplasm where it binds to the proapoptotic AES-TLE complex and enhances anoikis (11). This may be due to phosphorylation of Bit-1 by other signaling molecules such as PKD1 (13). However in cells attached to fibronectin, Bit-1 works in conjunction with a FAK/PI3K/NFB signaling pathway and elevates bcl-2 transcription to promote cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bit-1 and FAK also associated on collagen IV, suggesting that the signaling complex requires more than the physical association. Bit-1 phosphorylation by other proteins also may be involved (13). Integrin attachment promotes cell survival through the PI3K pathway via FAK, and both ␣5␀1 and ␣v␀3 pro-survival signals are through PI3K (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffiths and colleagues demonstrated that the NF-ÎșB pathway plays an important role in Bit1-mediated cell survival [14]. Hector Biliran et.al reported that protein kinase 1(PKD) is a positive regulator of Bit1 apoptotic functions [15], while according to Rania Kairouz-Wahbe, Bit1 can negatively regulate Erk activity [16]. Such investigations suggest that Bit1-induced anoikis is controlled by sophisticated regulation network, and is closely associated with other pathways and cell activities.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that PKD1-Ser 910 phosphorylation increases in the context of PKD1 activation by growth factor receptors or phorbol esters and that constitutively active forms of PKD1 (such as the PH domain-deleted or S738E/S742E-substituted mutants) display high levels of basal Ser 910 phosphorylation led to the widespread use of PKD1-Ser 910 phosphorylation as a surrogate marker of A, G protein-coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs) activate PKD1 via an allosteric mechanism involving lipid cofactors and phosphorylation by nPKC isoforms. PKD1 then phosphorylates a range of cellular substrates, including HDAC5, the sarcomeric proteins cTnI and cardiac myosin binding protein-C (cMyBP-C), CREB, the 27-kDa heat shock protein (HSP27), p21 protein (Cdc42/Rac)-activated kinase 4 (PAK4), cJun, Bit1 (Bcl-2 inhibitor of transcription, a mitochondrial protein that induces caspase-independent apoptosis), the F-actin-binding protein cortactin, the cofillin phosphatase slingshot 1, RIN1 (a Ras effector protein that influences ERK and c-Abl pathways), and the p85 regulatory subunit of PI3K (which is inhibited-no longer binds to RTKs-when phosphorylated in the SH2 domain by PKD1); direct substrates of PKD1 are in pink (Hurd et al, 2002;Döppler et al, 2005;Biliran et al, 2008;Eiseler et al, 2009Eiseler et al, , 2010Peterburs et al, 2009;BariĆĄić et al, 2011;Lee et al, 2011;Spratley et al, 2011;Ziegler et al, 2011). B and C depict alternative mechanism for PKD1 regulation by reactive oxygen species (ROS) or caspase-3 in the setting of oxidative stress or apoptosis (see Other PKD1 Activation Mechanisms).…”
Section: Mechanisms and Consequences Of Pkd1-ser 910mentioning
confidence: 99%